2019
DOI: 10.20944/preprints201911.0135.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Increased Levels of Plasma Tumor Necrosis Factor-α Mediate Schizophrenia Symptom Dimensions and Neurocognitive Impairments and Are Inversely Associated with Natural IgM and Paraoxonase 1 Activity

Abstract: Accumulating evidence suggests that TNF-α-mediated immune-neurotoxicity contributes to cognitive impairments and the overall severity of schizophrenia (OSOS). There are no data whether peripheral IL-6 and IL-4 may affect the phenome of schizophrenia above and beyond the effects of TNF-α and whether those cytokines are regulated by lowered natural IgM to malondialdehyde (MDA) and paraoxonase 1 enzyme activity. We assessed the aforementioned biomarkers in schizophrenia patients with (n=40) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…on the 6 OS variables (even without FDR correction). In previous studies using the same study sample we showed that there were no significant effects of the drug state on the other biomarkers listed in table 1 [4,11]. Table 4 shows significant logistic regression models predicting deficit schizophrenia using different biomarkers sets.…”
Section: Ostox and 3antiox In Deficit And Non-deficit Schizophreniamentioning
confidence: 80%
See 3 more Smart Citations
“…on the 6 OS variables (even without FDR correction). In previous studies using the same study sample we showed that there were no significant effects of the drug state on the other biomarkers listed in table 1 [4,11]. Table 4 shows significant logistic regression models predicting deficit schizophrenia using different biomarkers sets.…”
Section: Ostox and 3antiox In Deficit And Non-deficit Schizophreniamentioning
confidence: 80%
“…TNF-α, IL-6 and CCL11 (R&D Systems, Inc, Minneapolis, MN, USA) were measured using the Bio-Plex ® 200 System (Bio-Rad Laboratories, Inc.) as described previously [9,11]. IgM levels directed to conjugated MDA were assayed using an indirect enzyme-linked immunosorbent assay as described previously [10].…”
Section: Assaysmentioning
confidence: 99%
See 2 more Smart Citations
“…The same disorders in LINE 1 partial methylation patterns are detected in MIP and paranoid schizophrenia and are more pronounced in the latter . Schizophrenia may result from neurotoxic processes (Maes, Sirivichayakul et al 2020) and MA usage has neurotoxic effects on cortical interneurons (Hsieh, Stein et al 2014). Activated immune-inflammatory and neuro-oxidative stress play a role not only in schizophrenia or schizophrenia phenotypes (Maes, Sirivichayakul et al 2020, Ermakov, Dmitrieva et al 2021, Cuenod, Steullet et al 2022) but also in MA dependence , Afzali, Fadaei et al 2022.…”
Section: Introductionmentioning
confidence: 99%